Effect of Ethylene Glycol (EG) on the Viability of Mammalian Embryo during Cryopreservation - Hyun Kim; Young Moo Cho; Yeoung-Gyu Ko; Sung Woo Kim; Hwan-Hoo Seong; Keitaro Yamanouchi (The Korean Society of Animal Reproduction and Biotechnology, 2014)
Ethylene glycol (EG) has been successfully used as a cryoprotectant for vitrification of mammalian embryos (including human embryos) due to its low formula weight and high permeation into cells compared with other cryoprotectants, including propylene glycol (PROH). Cryopreservation is able to store the surplus pre-embryos for freezing and furthermore thawing and transfer in a subsequent cycle. This study was carried out to evaluate the effects of embryonic stage, cryoprotectant, and freezing-thawing method on the rates of survival and development of the cryopreserved mouse early embryo and finally to establish the cryopreservation method of surplus embryos obtained during assisted reproductive technology (ART). Female ICR mice (6~8 weeks old) were induced to superovulate by sequential intraperitoneal injection of 5 IU PMSG and 5 IU hCG 48 h apart. Mouse embryos were collected according to its developmental stage after the injection of hCG. Embryos were cryopreserved not only during cryoprotectant step (1~4 step) but also in a variety of media (HTF, IVF medium, D-PBS) and cell stage. The results were as follows : There is no clear advantage in these freezing media of rapid method, but 4 cell and 8 cell of slow method (2, 3 and 4 step) have advantage in D-PBS. The development of embryos according to cell stage become greater in 8 cell stage. In the treatment steps of cryopreservation, the development of embryo to blastocyst was similar among rapid method, but the development of 4 cell and 8 cell embryos to blastocyst according to slow method was better than rapid method.